2022
DOI: 10.1016/j.sjbs.2021.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D2 protects acute and repeated noise stress induced behavioral, biochemical, and histopathological alterations: Possible antioxidant effect

Abstract: Noise is an environmental stressor which causes distress and hearing loss in individuals residing in urban areas. Psychological deficits such as anxiety, depression, impaired memory and cognitive decline are caused by noise stress. Different vitamins have been used as a potential antioxidant for neuronal protection. In this study we investigate the anxiolytic, antidepressant and memory enhancing effect of vitamin D2 (Vit D2) following noise stress. Thirty-six albino rats were randomly divided into six groups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 61 publications
(72 reference statements)
1
14
0
Order By: Relevance
“…The acute NS-induced model of Samad et al [ 20 ] was used with slight adjustments to assess the protective outcomes of CLAE following the NS-induced behavioral and cognitive deficits in SD male rats (weighing 150–200 g). For this experiment, thirty arbitrarily selected rats were divided into five groups ( n = 5 in each group).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The acute NS-induced model of Samad et al [ 20 ] was used with slight adjustments to assess the protective outcomes of CLAE following the NS-induced behavioral and cognitive deficits in SD male rats (weighing 150–200 g). For this experiment, thirty arbitrarily selected rats were divided into five groups ( n = 5 in each group).…”
Section: Methodsmentioning
confidence: 99%
“…The noise level was set to 100 dB (3 KHz). A sound level meter (Smart Tools Co., Saitama, Japan; Range: 80–120 dB) with an accuracy of 30 Hz (±1.3 dB) was used to monitor the sound intensity [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, people gradually paid more attention to the researches on VitD2. Studies have shown that oral administration of VitD2 in rats had anti-anxiety, anti-depressant and memory-enhancing effects after noise stimulation [ 13 ]. According to Balachandar, VitD3 had higher efficacy in improving total 25(OH)D and reducing serum parathyroid level, comparing to VitD2 [ 14 ].…”
Section: The Metabolic Process Of Vitdmentioning
confidence: 99%